Analysis of criteria for determining a TNT equivalent - Panowicz, Robert (Strojniški vestnik, 2017)
The ConWep method is one of the most frequently used methods of modelling the effects of a blast wave impulse on a structure. The main goal of the study was to assess a TNT equivalent used in this approach. Six different methods to calculate this parameter for different explosive materials and charge shapes were analysed in this paper. The results error was lower than 20 % only when a TNT equivalent based on comparing the pressure impulses was used. This error can be lower only for spherical charges. In addition, for the tested distances (25 cm to 40 cm), TNT equivalents with an error margin of 5 % were assessed.
Keywords: ALE; eksploziv; metoda ConWep; MKE; TNT ekvivalent; udarni val